COMMUNITY SERVICE ACTIVITIES “SOCIALIZATION AVOID STUDY INVESTMENT” TO THE STUDENT BOND OF SERDANG BEDAGAI - Nur ilham, Rico; Likdanawati, Likdanawati; Hamdiah, Hamdiah; Adnan, Adnan; Sinta, Irada (RADJA PUBLIKA, 2022)
This paper explores investments that are full of manipulation and embezzlement. The reality of fraudulent investment development is considered to never die, even the number of victims and losses from year to year is getting more fantastic in some areas. The fact that there are so many victims and fantastic losses in these fraudulent investment offenses is analyzed, elaborated and formulated using common sense tools.This community service activity is carried out, so that the community is not badly affected by this fraudulent investment, this socialization is carried out so that people are careful about this fraudulent investment.